Fourth Five-Year Plan (1969-74) Tamil Nadu Draft Outline - Planning Commission (Planning Commission, 1969)
From the point of view of rainfall, Madras State has three distinct seasons—(i) advancing monsoon season (South-west winds)—June to September, (ii) retreating monsoon season (North-eastern winds)—October to January and (iii) transitional dry season (February to May). The south-west winds are descending winds blowing on the leeward side of the Western Ghats and hence give little rain unless they are forced to ascend by the intervening groups of bills. The heaviest rainfall of this season occurs in the high hills of Nilgiris district because of its direct exposure to south-west winds. The northern part of Coimbatore district, Salem and part of Tiruchirappalli district get more rainfall during the advancing monsoon season than during the retreating monsoon season. The rainfall of the retreating monsoon is closely associated with seasonal depressions in the Bay of Bengal round which humid currents of the retreating monsoon blow towards the east coast of this region. Since the direction is either easterly or north easterly, rainfall is heaviest along the east coast and declines steadily in the interior till it ascends up the Ghats. During the hot weather season, climate is generally dry interrupted by thunder-storms whose frequencies increase rapidly with the increase of temperature. Broadly speaking Nilgiris district and Palani taluk of Madurai district receive the highest amount of rainfall. The east coast ranks next in regard to rainfall. The third area of medium rainfall is Kanyakumari in the south-west. The whole of the interior plateau is an area of low rainfall amidst which there are two pockets of very low rainfall, one in Coimbatore district and the other in Ramanathapuram district. Planning in Madras State has to take note of this crucial fact that over bulk of the area of the State, the rainfall is low and protective irrigation through tanks or simple wells or deep bore wells is an essential pre-requisite for successful implementation of any programme for modernisation of agriculture.
Draft Outline
Government of Tamil Nadu